Characterization of cumulus cloud fields using trajectories in the center of gravity versus water mass phase space: 1. Cloud tracking and phase space description - Heiblum, RH; Altaratz, O; Koren, I; Feingold, G; Kostinski, AB; Khain, AP; Ovchinnikov, M; Fredj, E; Dagan, G; Pinto, L; Yaish, R; Chen, Q (Wiley, 2016)
We study the evolution of warmconvective cloud fields using large eddy simulations of continental and trade cumulus. Individual clouds are tracked a posteriori from formation to dissipation using a 3-D cloud-tracking algorithm, and results are presented in the phase space of center of gravity altitude versus cloud liquid watermass (CvMspace). The CvMspace is shown to contain rich information on cloud field characteristics, cloud morphology, and common cloud development pathways, together facilitating a comprehensive understanding of the cloud field. In this part we show how themeteorological (thermodynamic) conditions that determine the cloud properties are projected on the CvMphase space and how changes in the initial conditions affect the clouds’ trajectories in this space. This part sets the stage for a detailed microphysical analysis that will be shown in part II.